7 Relation between N-terminal pro B-type natriuretic peptide (NT-probnp) and disease severity in paediatric hypertrophic cardiomyopathy. (4th June 2021) - Kaliyappan, Laxmi; Watson, Sarah; Fiend, Ella; Norrish, Gabrielle; Cervi, Elena; Kaski, Juan
Abstract : Introduction: N-terminal pro B-type natriuretic peptide (NT-proBNP) is associated with an increased risk of mortality and heart failure related adverse events in adults with hypertrophic cardiomyopathy (HCM). Elevated NT-proBNP levels have been correlated with multiple subjective and objective parameters of HCM severity including dyspnoea and left ventricular maximal wall thickness (LVMWT). However, robust prognostic markers in adults may not be reliable for children with HCM in whom disease severity assessment is challenging. No studies have yet evaluated utility of NT-proBNP in children with HCM. Thus, the objective of this study was to assess associations of NT-proBNP with conventional markers of disease severity and predictive ability of NT-proBNP in a paediatric HCM cohort. Methods: Plasma NT-proBNP levels were measured in eighty consecutive patients [23 (28.8%) females; median age: 12.3 years (interquartile range (IQR): 6.4-16.0); 37 (46.3%) sarcomeric aetiology]. Contemporaneous data from conventional clinical evaluation was used to establish disease severity including electrocardiography, echocardiography, tissue Doppler imaging, magnetic resonance imaging (MRI) and cardiopulmonary exercise testing. Results: Median NT-proBNP concentration was 1104.5 pg/mL (range: 20–11206 pg/mL and IQR: 108.5–2613.5 pg/mL). NT-proBNP levels correlated with: QTc (ρ= 0.445, p<0.01); septal thickness z-score (ρ=0.618, p<0.001); MLVWT z-score (ρ=0.582, p<0.001); lateral S' (ρ=–0.668, p<0.001); septal E/E' (ρ=0.609, p<0.001); MRI MWT (ρ=0.773, p<0.001; indexed LV mass (ρ=0.576, p<0.001) and peak systolic blood pressure (ρ=–0.605, p<0.001). There were weak associations between NT-proBNP and aetiology or subjective symptoms including palpitations and chest pain (p>0.05). NT-proBNP levels were higher in patients who were: female; dyspnoeic (defined as Ross/NYHA Class ≥II); prescribed cardioactive medication and had an implantable cardioverter defibrillator (p<0.05).Lateral S' (β = –0.306, p=0.001) and MLVWT (β = 0.217, p = 0.013) were independent predictors of NT-proBNP in multivariate analysis. At a cut-off point of 300 pg/ml, NT-proBNP had a positive predictive value of 84% and a negative predictive value of 72% for predicting septal E/E'>10 (Area under the curve = 0.775 (p<0.001)) (See figure 1 ). Conclusions: NT-proBNP levels correlate with parameters of disease severity in paediatric HCM including measures of diastolic dysfunction (septal E/E') and systolic dysfunction (lateral S'). NT-proBNP measurement may be an effective adjunct for monitoring disease severity in children, particularly when conventional clinical evaluation is challenging. Future studies in larger cohorts of children are needed to explore prognostic value. Conflict of Interest: None